Othermothering and Othermothers in the Harry Potter Series - Lacassagne, Aurélie (Journal of the Motherhood Initiative for Research and Community Involvement, 2016)
The Harry Potter series quickly became a classic of children’s literature and remains to date the most read work in the history of literature. That is certainly a good reason to examine more closely its representations of mothers and motherhood. In this paper, I argue that maternal practices and representations, particularly of othermother figures and othermothering practices, are central to the Harry Potter series and that they have specific psychological and social functions. I propose a typology of othermothers portrayed in this literary work. I then explore the psychological functions of other- mothers for readers. Lastly, I show the paramount role played by othermothers in social and political mobilization.